Assessing The Efficiency and Impact of The Revenue Cycle Management (RCM) Model in Hospitals - Uma , Dr.S.; Damodaraswamy , Dr. Anandhi; Lekshmi , Dr.R.S.; Maurya , Dr. Shyam; Anand , Dr. Utkarsh (International Journal of Accounting and Economics Studies, 2025)
Revenue cycle management (RCM) plays an important role in ensuring the financial stability and operational efficiency of hospitals. This study evaluates the effectiveness of RCM models in revenue production, reducing claims refusal, and improving cash flow in healthcare institutions. Through a qualitative and quantitative approach, the study analyzes major performance indicators such as billing accuracy, reimbursement rates, and time of collection. Conclusions suggest that successful RCM implementation increases financial performance, reduces administrative burden, and the patient streamlines payment processes. Nonetheless, to achieve the best outcomes, organizations must tackle ongoing hurdles in regulatory compliance, seamless technical integration, and comprehensive staff training. The study therefore recommends boosting revenue-cycle-management efficiency through strategic automation, consistent policy standardization, and robust, ongoing training initiatives for all personnel.